Marine habitats and related fishery resources in Ly Son and adjacent waters in the Northern part of Quang Ngai province - Long, Nguyen Van; Thai, Minh Quang; Mai, Xuan Dat; Tong, Phuoc Hoang Son (Vietnam Journal of Marine Science and Technology, 2022)
The study assessed the distribution of key marine habitats and related fishery resources and spawning and nursery grounds of target species in the waters of Ly Son islands and adjacent locations of Tra Bong and Sa Ky estuaries using data from analysis of the Sentinel-2 satellite image and ground-truthing. There were about 1,787 ha of coral reefs, 117.3 ha of seagrass beds, and 309 ha of nipa palm (Nypa fruticans) distributed in this area, in which the water surrounding Ly Son marine protected area (MPA) supported more than 1,706 ha of coral reefs and 116 ha of seagrass beds. The area also supported 12 nursery grounds of 10 target resources, including giant trevally, mangrove-red snapper, orange-spotted spinefoot, orange-spotted grouper, malabar grouper, barramundi related to nipa palms in Tra Bong and Sa Ky estuaries. In contrast, sea cucumbers, turbo snails, top shells, and giant clams were associated with coral reefs in Ly Son MPA. Related fishery resources, spawning, and nursery grounds of target species involved 8 consultations of local experienced fishermen and a field investigation of the presence of spawning and nursery grounds from November 2019 to September 2020. A total of 1,278 tonnes of commercial resources were harvested in the coral reefs and some 4.647 thousand juveniles of fish and crabs were collected from the adjacent estuaries, in which some essential species of reef fishes indicate linkages between juveniles collected from the nipa palm and seagrass beds in Tra Bong and Sa Ky estuaries and adults fished in the coral reefs in Ly Son MPA. So, conservation and management of exploitation of fish juveniles related to the nipa palm and seagrass beds in Tra Bong and Sa Ky estuaries are considered important solutions for the maintenance of the linkages of fish resources associated with critical marine habitats and fisheries in the waters of Ly Son MPA and adjacent locations in the future.